Dampak Realisasi Belanja Bantuan Sosial Pangan terhadap Indeks Pembangunan Manusia di Indonesia - Dwilaksmi, Anandi; Nabilah, Alifia Agnes; Sihaloho, Estro Dariatno (Universitas Pasundan, 2025)
The purpose of this study is to evaluate the importance of the relationship between Indonesia's Human Development Index (HDI) and government spending on food assistance. This study uses the Panel Data Regression approach to aggregate cross-sectional data from 34 provinces throughout the years 2018–2022. The data utilized in this investigation came from the Ministry of Finance (KEMENKEU) and Statistics Indonesia (BPS) sources. This study found that food social assistance has a positive influence on HDI. School Expectancy, the School Operational Assistance (BOS) budget, and the Health Operational Assistance budget (BOK) also have a positive influence on HDI. Meanwhile, the poverty rate has a negative influence on HDI. As indicated by the rise in the HDI, the study's findings suggest that the government's implementation of Social Food Assistance spending has a beneficial effect on raising the standard of human development in Indonesia.